Differential diagnosis of PRKAG2 Cardiac syndrome in hypertrophic cardiomyopathy patients of han nationality - Xue-Jie Li; Nian-Wei Zhou; Hui-Lin Xie; Wen Liu; Cui-Zhen Pan; Xian-Hong Shu (Cardiology Plus, 2021)
Objectives: This study aimed to diversify the spectrum of PRKAG2 variants and explore its clinical features in a Chinese Han population with hypertrophic cardiomyopathy (HCM). Methods: Whole-exome sequencing was performed on 200 patients diagnosed with HCM, and four causative PRKAG2 variants were identified in the probands and their relatives using Sanger sequencing. Their clinical manifestations, laboratory examinations, therapeutic methods, and outcomes were documented and analyzed. Results: Four variants were identified in six probands and seven of their relatives. Left ventricular hypertrophy was present in all probands. Five probands had sinus bradycardia, three had implanted pacemakers (PM), one developed heart failure, two had ventricular preexcitation, and one had atrial fibrillation. Conclusions: PRKAG2 cardiac syndrome (PCS) is a rare autosomal dominant disease characterized by ventricular hypertrophy, preexcitation, and progressive conduction defects, resulting in a high incidence of PM implantation. Genetic testing provides robust information for distinguishing PCS from sarcomeric HCM, which will be beneficial in guiding therapy and improving prognosis.